Implementation MBKM Curriculum Exploring the Industrial Mindset in Islamic Education at UIN Sunan Kalijaga Yogyakarta - Kuncoro, Irfan; Wahidmurni, Wahidmurni; Hady, M. Samsul (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
The rapid flow of industrialization in several sectors, including education, educational institutions, especially PTKI, must balance the education system with the times, which is expected to be able to give birth to creative and innovative students. This research is a field study that aims to reveal the concept of MBKM at UIN Sunan Kalijaga. Data was collected through in-depth interviews with the Head of the Study Program, the Head of LPM, the Dean, and the Students. This article aims to analyze the concept of independent learning on an independent campus (MBKM) in more depth, tracing the industrial mindset at UIN Sunan Kalijaga. The study results show that the industrialization of education is conspicuous in the MBKM policy implemented at UIN Sunan Kalijaga. This is seen from the industrial factor, which is of great concern in educational design, meaning that national education only determines students to become skilled workers as the main objective, contrary to the objectives of national education in Bill 20 of 2003, which contains that the purpose of education is to form character and personality as a priority as teachings in Islam. The MBKM programs at UIN Sunan Kalijaga also emphasize that skilled workers must meet the demands of the business and industrial world as an integral part of alleviating unemployment. It is different from the teachings of Islam through the continuous messages of Muslim scholars that education aims to give birth to perfect humans.